Smoking and Cellular Telephone Use Among Pregnant Women Seeking Prenatal Care: Opportunities for Intervention. (December 2015) - Gilbert, Jennifer; Schnoll, Robert; Morrison, Mary F.; Srinivas, Sindhu K.; Pond, Timothy; Curtis, Brenda; Henry, Jennifer; Kranzler, Henry R.
Abstract : Objectives: Although smoking during pregnancy is associated with poor pregnancy outcomes, many women continue to smoke throughout pregnancy. Behavioral interventions for smoking cessation yield modest benefits, particularly in lower socioeconomic groups. Pharmacotherapy, a first-line option for smoking cessation, has not shown clear benefits for pregnant smokers, partly due to limited adherence. We evaluated the feasibility of conducting a pharmacotherapy trial for smoking cessation in pregnant women, using text messaging to enhance medication adherence. Materials and Methods: We surveyed 724 predominantly minority pregnant women to examine the prevalence and correlates of smoking and the use of cellular telephones and text messaging. Results: Nearly 18% of the respondents were current smokers, with a majority (67.7%) expressing interest in participating in a smoking cessation trial. Only about 6% of women with a smoking history ever received nicotine dependence treatment. Smokers were significantly more likely to be depressed than nonsmokers. The vast majority of respondents (92.1%) owned cell phones, with 93.2% having an unlimited text messaging plan. Conclusions: These data support the feasibility of conducting a pharmacotherapy smoking cessation trial and using text messaging to enhance medication adherence in a predominantly minority population of pregnant smokers.